ENGAGE AF-TIMI 48: Edoxaban Safe and Effective in Elderly Patients with AF - Mosley, Mary (MD Conference Express, 2014)
Atrial fibrillation (AF) becomes more common with increasing age. Data from an unpublished new analysis of the Global Study to Assess the Safety and Effectiveness of Edoxaban (DU-176b) vs Standard Practice of Dosing With Warfarin in Patients With Atrial Fibrillation [ENGAGE AF-TIMI 48] support edoxaban as an alternative treatment to warfarin in elderly patients who require anticoagulation therapy. This article discusses a prespecified analysis that evaluated the association of age on study outcomes and the efficacy and safety of edoxaban relative to warfarin in the elderly with AF.